Acute high-grade acromioclavicular dislocations treated with triple button device (MINAR): Preliminary results. Issue 11 (November 2016) - Cano-Martínez, José Antonio; Nicolás-Serrano, Gregorio; Bento-Gerard, Julio; Picazo-Marín, Francisco; Andrés-Grau, Josefina
Abstract: Objective: Describe the clinical and radiological results of triple button device in the treatment of high-grade AC dislocations (Rockwood, type V) and assess whether improves vertical and horizontal stability compared to the techniques previously described. Material and methods: This retrospective study included 39 patients with type V acromioclavicular dislocations treated with Twin Tail TightRope™ system (triple button device). Of the 39 patients, 33 (26 men and 7 women) were able to participate in clinical and radiographic follow up. At the time of surgery, the mean age was 25 years ± 7 (range, 17–49). All patients underwent bilateral-weighted Zanca (CC distance) and Alexander view (AC distance) as well as the Constant Score (CS) and Acromioclavicular Joint Instability Scoring System (ACJI). Radiological and clinical outcome was assessed during routine follow-up examinations preoperatively, postoperatively, 1, 3, 6 months and every year after the surgery. The presence of calcification, degenerative changes, mobilization of implants and bone resorption were also assessed. Results: After a mean follow up of 25 ± 4 months (range 14–38), the results of the Constant (CS) were 94.1 ± 5, 5 (range 76–100) and test ACJI 87.3 ± 9, 8 (range 65–100), showing no significant differences with the uninjured shoulder (CS 95.8 ± 2.5, range 83–100; ACJI 94.1 ± 3.7, range 80–100). At final review, we observed that preoperative coracoclavicular distance (Zanca View) improved from 21, 75 ± 1.97 mm to 8, 73 mm ± 0.75 and the acromioclavicular distance (Alexander View) from 12, 65 mm ± 1.99 to 0, 35 ± 0.3 mm. Compared with healthy shoulder, these differences were not significant. There was no loss of reduction with this system in the vertical plane. 4 patients (12.12%) revealed signs of posterior instability with worse clinical test results. The presence of degenerative joint changes (6, 06%), calcifications (27, 2%) or mobilization of the implant (18, 18%) was not associated with worse clinical outcomes. Conclusion: Twin Tail device using minimally invasive technique improves stability in the vertical and, specially in the horizontal plane relative to the previously described techniques without increasing number of complications.